Mathematical model of Mobile Circulatory Module for ex-vivo lungs perfusion - Šolc, František; Zezulka, František; Veselý, Ivo (IFAC, 2015)
The article deals with mathematical modelling of a system for ex-vivo lung perfusion. The system which is modelled here is named Mobile Circulatory Module and is designed for transport of live lungs namely porcine or human lungs. Transported lungs should be used for various research or even for transplantation. The article describes mathematical model of thermal circuit and hydraulic circuit which are vital parts of the MCM to secure living conditions of the transported organ. Mathematical model is simulated with MATLAB Simulink and shows good qualitative correspondence with real behavior of the system. Based on math model there is designed control algorithm for temperature control and there is discussed control of perfusion liquid as well.

The article deals with mathematical modelling of a system for ex-vivo lung perfusion. The system which is modelled here is named Mobile Circulatory Module and is designed for transport of live lungs namely porcine or human lungs. Transported lungs should be used for various research or even for transplantation. The article describes mathematical model of thermal circuit and hydraulic circuit which are vital parts of the MCM to secure living conditions of the transported organ. Mathematical model is simulated with MATLAB Simulink and shows good qualitative correspondence with real behavior of the system. Based on math model there is designed control algorithm for temperature control and there is discussed control of perfusion liquid as well.
Mathematical model of Mobile Circulatory Module for ex-vivo lungs perfusion
Keywords: ex-vivo lungs perfusion; isolated organ; MCM; Matlab model; control of flow; temperature control; ex-vivo lungs perfusion; isolated organ; MCM; Matlab model; control of flow; temperature control